2000
DOI: 10.1108/00070700010332278
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of fresh meat quality: cross‐national comparison

Abstract: This paper summarises the results of the consumer survey, which had been carried out in six European countries in order to obtain comparable information about consumer behaviour towards meat and perception of fresh meat quality. Quality evaluation of fresh meat in this study is supposed to consist of two phases: a stage previous to the actual purchase and a stage after the purchase while eating the meat. Concerning the first stage, it becomes obvious that for beef and pork the place of purchase plays a major r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
120
2
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 1 publication
17
120
2
9
Order By: Relevance
“…Egan et al (2001) mentioned that the eating quality of beef may improve through marbling because of increased juiciness and flavor. Glitsch (2000) also demonstrated that leanness was more often associated with the purchase of chicken meat. Similarly, Kennedy et al (2004) found that leanness (less fat content) was one of the main reasons why consumers chose chicken over red meats.…”
Section: Insert Table 6 About Here --------------------------------mentioning
confidence: 89%
See 2 more Smart Citations
“…Egan et al (2001) mentioned that the eating quality of beef may improve through marbling because of increased juiciness and flavor. Glitsch (2000) also demonstrated that leanness was more often associated with the purchase of chicken meat. Similarly, Kennedy et al (2004) found that leanness (less fat content) was one of the main reasons why consumers chose chicken over red meats.…”
Section: Insert Table 6 About Here --------------------------------mentioning
confidence: 89%
“…Freshness was a major criteria in assessing the perceived safety of beef, pork and chicken among European consumers (Glitsch 2000). Anklam and Battaglia (2001) found that consumers' expected high quality food to be fresh, good looking, nutritious, wholesome, tasty and most importantly to be safe.…”
Section: About Here --------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…This does not mean that consumers care less about the price when thinking about meat, for as indicated by Becker (1999), consumers do not always assume that a higher price will lead to superior quality. Glitsch (2000) revealed that price was regarded as being the least helpful for assessing the quality of meat.…”
Section: Here --------------------------------mentioning
confidence: 99%
“…Examples include data from works of agro-food products such as wine (Verdú, Llorens, & Fuentes, 2004), fruit and vegetables (Sule, Paquin, & Levy, 2002Sule, Muñoz, & Levy, 2005) and meat (Becker, 2000;Hoffmann, 2000;Glitsch, 2000). It should be pointed out that in this respect, however, the key factor being the time and place where the consumer receives all information on the food product, information from more or less distorted perception of extrinsic and intrinsic attributes product, which significantly affect the buying process.…”
Section: Perceived Quality Of Minimally Processed Vegetable Productsmentioning
confidence: 99%